We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

how do I solve for x in this... xy+5=x+7? I cant figure it out and I really need help.

Braksess Oct 12, 2014

#7**+5 **

Hi Braksess,

I really like your dogged determination to understand this!

I think you are having problems with this

$$xy-x=x(y-1)$$

so that is the bit I am going to look at.

Look at the rectangle below.

The area of the whole rectangle is $$x\times y \quad units^2$$

I have cut a little rectangle off the end. The area of the cut off bit is $$1\times x=x \quad units^2$$

so the area that is left when you take away the litle bit at the end is

$$\\x\times y - x\\

or\; just\\ xy-x$$

The area that is left after you take away the bit at the end is displayed in yellow below.

The length of the top is y-1 (because 1 unit was cut off)

The side is still x units

The area is x(y-1)

SO $$xy-x=x(y-1)$$

LETS look at it the other way around

you probably know that 3(x-1)=3*x-3*1 = 3x-3

It works with letters too

$$x(y-1)=x\times y - x\times 1 = xy-x$$

NOW lets look at how to factorise it going in the other direction.

$$\\xy-x=x\times y - x\times 1\\

$x is a common factor so we can factor it out and we will be left with $y-1$ in the bracket.$\\

=x(y-1)$$

Melody Oct 14, 2014

#1**+5 **

To solve for x, get all the x-terms to one side and everything else to the other side:

xy + 5 = x + 7

Subtract 5 from both sides:

xy = x + 2

Subtract x from both sides:

xy - x = 2

Factor out the x:

x(y - 1) = 2

Divide both sides by y - 1:

x = 2 / (y - 1)

geno3141 Oct 12, 2014

#3**+5 **

I think you're getting a little confused here, Braksess....here's what geno did

xy = x + 2 ( subtract x from both sides )

-x -x

------------

xy - x = 2 (note that he didn't "divide away" x......I think this is what you were thinking......!)

Can you take it from here??

CPhill Oct 13, 2014

#4**0 **

y=2? i know im wrong but im still really confused, xy/-x=x-2/x im trying to find x. maybe its x-x=-y-2...so....0=y-2

Braksess Oct 13, 2014

#5**+5 **

Let's try this again.............

Note that we have......

xy + 5 = x + 7 now....just subtract 5 from both sides....

-5 = -5

--------------------

xy = x + 2

Now...I want to get rid of the x on the right side.....so I can just subtract it from both sides...so we have

xy = x + 2

-x -x

------------------

xy - x = 2 Notice how the x "disappeared from the right and ended up on the left as a "negative??"

Now...I just want to "factor the x on the left out of both terms....so we have....

x(y - 1) = 2 do you see that???

So this is like having

x * (y - 1) = 2 and since I want the "x" by itself on the left....we can * divide* both sides by (y - 1)

So

x* (y - 1)/(y-1) = 2/(y-1) and the (y -1)s on the left "cancel" leaving us with......

x = 2/(y - 1) !!!!

Does that help ???

(We can't get any "numerical" values for x or y, because we don't know the value of either !!!! )

CPhill Oct 13, 2014

#7**+5 **

Best Answer

Hi Braksess,

I really like your dogged determination to understand this!

I think you are having problems with this

$$xy-x=x(y-1)$$

so that is the bit I am going to look at.

Look at the rectangle below.

The area of the whole rectangle is $$x\times y \quad units^2$$

I have cut a little rectangle off the end. The area of the cut off bit is $$1\times x=x \quad units^2$$

so the area that is left when you take away the litle bit at the end is

$$\\x\times y - x\\

or\; just\\ xy-x$$

The area that is left after you take away the bit at the end is displayed in yellow below.

The length of the top is y-1 (because 1 unit was cut off)

The side is still x units

The area is x(y-1)

SO $$xy-x=x(y-1)$$

LETS look at it the other way around

you probably know that 3(x-1)=3*x-3*1 = 3x-3

It works with letters too

$$x(y-1)=x\times y - x\times 1 = xy-x$$

NOW lets look at how to factorise it going in the other direction.

$$\\xy-x=x\times y - x\times 1\\

$x is a common factor so we can factor it out and we will be left with $y-1$ in the bracket.$\\

=x(y-1)$$

Melody Oct 14, 2014